From Students To Talent: Orchestrating Human Capital For The Technopreneurial University Transformation - Eddy Soeryanto Soegoto; Rahma Wahdiniwaty; Irfan Dwiguna Sumitra; Adam Mukharil Bachtiar; Puri Swastika Gusti Krisna Dewi; Imanuel Eko Anggun Sugiyono (Pascasarjana STIE Amkop Makassar, 2026)
This research focuses on testing the effectiveness of the Student-HRM framework—Competency Development, Incentive Support, and Innovation-based Assessment—in influencing multidimensional transformation of student technopreneurship (Culture, Digital Readiness, and Innovation Ecosystem) in higher education institutions. Based on a quantitative explanatory design, data were obtained from 100 undergraduate students who are actively involved with digital entrepreneurship programs through a purposive sampling technique. The conceptual model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4 to assess the measurement model and evaluate the structural path coefficients by a bootstrapping procedure using 5,000 subsamples. The structural model shows significant predictive power (R2 > 0.70). The results highlighted a surprising paradox: Competency Development Support did not contribute significantly to transformation in any dimension, therefore questioning the ingrained belief that training alone leads to readiness. On the other hand, Incentive and Appreciation Support emerged as the stronger predictor and significantly affected all three dimensions. Innovation-based Assessment, however, was effective only in shaping the Technopreneurship Culture but proved ineffective in improving Digital Readiness or Ecosystem engagement.